SIMULASI JARINGAN VPN ROUTER DENGAN METODE LINK STATE ROUTING PROTOCOL DI SMK KORPRI MAJALENGKA - dzulfiqri, moch; Nurdiana, Nunu (Universitas Majalengka, 2024)
At this time the progress of information technology is growing so rapidly. The internet is a product of advances in information technology that can be accessed by anyone and anywhere. The increasingly sophisticated information technology helps a lot in human life today, but not a few also have a negative impact on the individual and group levels. Therefore, it is necessary to have a data and information security system. SMK Korpri Majalengka is an education provider institution in Majalengka Regency that has not carried out a data communication security system that is not optimal, such as confidential data that can still be accessed by just anyone. The agency needs a local network that has a wide range, cannot be accessed by just anyone, but only people who have access rights are connected to the local network so that agency security can be maintained properly. To solve this problem, a Virtual Private Network (VPN) network is needed. Therefore, the author intends to answer the above problems by simulating the